PENGEMBANGAN MEDIA VIDEO ANIMASI MENGGUNAKAN RENDERFOREST PADA SUBTEMA PERKEMBANGAN TEKNOLOGI KOMUNIKASI - Septi Widia Risa; A. Gani, Resyi; Wijaya, Ade (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The goal is to develop animation video media using Renderforest on the subtheme of the development of communication technology and test the feasibility of the product. This study uses the R&D (Research and Development) research method with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model approach. This research was carried out at SDN Pasirangin on May 2, 2024, with 34 students in grades III-B for the 2023/2024 academic year. Qualitative data analysis techniques from observations and interviews, and quantitative data regarding the results of expert validation, teacher responses and student responses. Based on the results of the validation of media experts received a score of 80% with the criteria of 'feasible', the results of the validation of material experts received a score of 90% with the criteria of 'very feasible', and the results of the validation of linguists received a score of 100% with very feasible criteria. Animation video media using Renderforest is very feasible and can be tested for teachers and students. Based on the results of the trial through the questionnaire, the teacher's response received a score of 93.33% and the trial of the student's response received a score of 90% with very good criteria. Based on the results of the two trials, it can be concluded that the animated video media developed can make students understand the material described, feel enthusiastic and happy in participating in learning, so that the animated video media is very suitable for use in learning the subtheme of communication technology development.